Comprendre Le Role Des Systemes D’information Dans L’amelioration De La Performance Et La Maturite Des Processus Logistiques: Etude Qualitative Aupres De Six Entreprises De L’industrie Automobile Et Aeronautique Au Maroc - Boubker, Omar; Chafik, Khalid (European Scientific Journal, ESJ, 2016)
The main objective of this paper is to understand the process by which the logistics information systems contribute to the performance and process maturity. On the methodological plan, we adopted an exploratory qualitative approach, based on a sample of six companies in the automotive and aerospace industries in Morocco. The results assert that the logistics information systems use is highly dependent on several variables. Besides, they show that the user experience remains a central variable which influences the level of use, user satisfaction and level of logistics information quality perception. These results indicate that the issue of process maturity remains difficult to operationalize in the studied cases, something in which we found it necessary to merge the variables related to the performance and process maturity in a single variable called "logistics benefits".